Modeling and analysis of real-time and embedded systems with UML and MARTE : developing cyber-physical systems - Selic, Bran (Morgan Kaufmann, 2014)
This book explains how to apply the complex MARTE standard in practical situations. This approachable reference provides a handy user guide, illustrating with numerous examples how you can use MARTE to design and develop real-time and embedded systems and software.